Pengembangan Model Kelembagaan Kawasan Wisata Pangandaran Kabupaten Ciamis – Zulpikar - Zulpikar, Zulpikar (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2011)
Pangandaran, a tourist destination located in Ciamis Region,, becomes an important part in economic growth of West Java, Indonesia. Unfortunately, it is s not managed optimally, yet. Therefore, this paper suggests several organization models as alternatives for managing this area optimally.The methodology of the paper is qualitative research. The tool of analysis is case study. Primary data was collected through depth interview with the officials of Tourism and Culture Office of Ciamis Regency, and through Focus Group Discussion with several Regional Organizational Apparatus who were in the management team of Pangandaran Tourist Area. Whereas, secondary data was collected from some relevant documents.